2004
DOI: 10.1111/j.1442-9993.2004.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of season of burn on shoot recovery and post‐fire flowering performance in the resprouter Stirlingia latifolia R. Br. (Proteaceae)

Abstract: Stirlingia latifolia R. Br. is a proteaceous undershrub that is widespread in open woodlands and heathlands of the south-west botanical province of Western Australia where it is subject to frequent fires, both natural and the result of fuel-reduction burns. Shoots are completely destroyed by fire but regenerate rapidly by resprouting numerous new shoots from the root crown. Flowering is strongly triggered by fire with only sparse flowering in firefree periods. A study was undertaken to compare regrowth and flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
2
24
2
Order By: Relevance
“…In contrast to our results, other studies have shown that dormant or growing-season fires increased flowering among forb and/or shrub species (Bowen and Pate 2004;GlennLewin et al 1990;Lamont et al 2000;Menges and Root 2004;Platt et al 1988;Wrobleski and Kauffman 2003). Investigations into the cause of this effect have found that increased flowering is in response to increased light levels (Norden and Kirkman 2004), physical removal of stems (McConnell and Menges 2002), nutrient pulses and increased light promoting increased flowering (Verboom et al 2002) and season of burning relative to photoperiod (Risberg and Granström 2009).…”
Section: Burn Season Effects On Floweringcontrasting
confidence: 85%
See 1 more Smart Citation
“…In contrast to our results, other studies have shown that dormant or growing-season fires increased flowering among forb and/or shrub species (Bowen and Pate 2004;GlennLewin et al 1990;Lamont et al 2000;Menges and Root 2004;Platt et al 1988;Wrobleski and Kauffman 2003). Investigations into the cause of this effect have found that increased flowering is in response to increased light levels (Norden and Kirkman 2004), physical removal of stems (McConnell and Menges 2002), nutrient pulses and increased light promoting increased flowering (Verboom et al 2002) and season of burning relative to photoperiod (Risberg and Granström 2009).…”
Section: Burn Season Effects On Floweringcontrasting
confidence: 85%
“…latifolia Engl., and Rosa carolina L., was negatively impacted by early-and growing-season burns. In Australia, the effect of season of burning on flowering in the resprouter, Stirlingia latifolia, was related to length of time from the burn to the production of mature shoots that could bloom, a concept that seems important for oak savanna shrub resprouters as well (Bowen and Pate 2004). (3) Flower number was reduced a year after an early-season burn compared to a previous 5-year fire (early-season shrub flowering during PP1; Table 1).…”
Section: Burn Season Effects On Floweringmentioning
confidence: 97%
“…This can be interpreted as a proximate response to the increase in postfire resources available for production of the more resource-demanding female cones, which ultimately has adaptive significance. In a similar way, the fraction of bisexual flowers (and thus fruits) in the andromonoecious Stirling latifolia (Ladd and Connell 1993) increases markedly in response to fire (B. Lamont, unpublished) along with the escalated flowering response (Bowen and Pate 2004).…”
Section: Fitness Benefitsmentioning
confidence: 91%
“…Despite burning foliage able to reach[1,000°C in this species, the zone immediately above the apical bud remains below 60°C (Lamont et al 2004), implying that, if a heat pulse is required, the temperature reached by the apex will depend on the intensity of fire. Similarly, for the shrub, Stirlingia latifolia, 92% of plants burnt in summer/autumn flowered and 2% in winter so that Bowen and Pate (2004) suggested that the greater dry-season heat intensifies the physiological response responsible for morphogenesis. In a less seasonal climate, Gill et al (1981) recorded almost complete flowering of X. australis after spring and summer fires, but substantial flowering was delayed for 12 months after autumn and winter fires.…”
Section: Proximal Causes Of Floweringmentioning
confidence: 96%
“…Fire size, shape and spatial patterns affect recovering and seedling colonization of burned sites (Lavorel et al 1998). Furthermore, shoot recovery might be influenced by fire intensity and temperature (Bowen and Pate 2004).…”
Section: Introductionmentioning
confidence: 99%